Augmented Reality as a Medium for Integrating Local Wisdom and Tolerance in Elementary School Learning: A Systematic Literature Review - Mustafidah, Fina Zulfa; Dasna, I Wayan; Kuswandi, Dedi (Jurnal Locus Penelitian dan Pengabdian, 2026)
The rapid development of digital technology has driven the adoption of innovative learning media in elementary education, including Augmented Reality (AR). Although AR has been widely recognized for enhancing learning engagement and conceptual understanding, its integration with local wisdom and character education particularly tolerance remains limited in the Indonesian elementary school context. This study aims to systematically map research trends on the use of AR in elementary education that integrates local wisdom and tolerance values, as well as to identify existing research gaps that may inform future learning media development, especially those grounded in Panji Malang local wisdom. This study employed a Systematic Literature Review (SLR) following the PRISMA protocol. Through four stages of elimination, 32 empirical research articles published between 2016 and 2025 were selected. Data were analyzed using content analysis and bibliometric mapping with VOSviewer to identify publication trends, research methods, and thematic clusters. The findings indicate a growing interest in AR-based learning since 2022, with most studies focusing on technological development and learning effectiveness. However, the explicit integration of tolerance as an affective learning objective remains limited. Bibliometric analysis reveals three dominant clusters: technology-based learning, local wisdom and cultural values, and elementary school learning contexts. Overall, AR demonstrates strong potential as a medium for integrating local wisdom and tolerance values, though challenges related to teacher readiness, infrastructure, and long-term impact evaluation persist.